The Holistically Integrated Curriculum: Implications for Personality Development - Norsuhaily, Abu Bakar; Rahimah, Embong; Ibrahim, Mamat; Ruzilawati, Abu Bakar; Idris, Abd. Hamid (2015)
This paper aims to propose a renewed concept of ‘Holistic Integrated Curriculum’ (HIC) which will be useful for personality development in integration of the curriculum. It defines the concept of integrated curriculum from a holistic worldview, its theoretical framework and discusses the implications of this concept on personality development. The issue of defining integrated curriculum has received a massive amount of attention from educational theorist and scholars from the West since the turn of the twentieth century. Initially, the integrated curriculum has been practiced by most contemporary educational institutions around the world at all levels i.e. primary, secondary and tertiary. However, there is a great diversity in their curricula, objectives and contents. Hence their claims that their educational systems are fully integrated, brings about confusion. This leads to the first part of the discussion on revisiting the concept of HIC from a holistic worldview. The second part of the paper is an explanation of the theoretical framework. This renewed concept has a flexible theoretical framework which is divided into seven essential components and seven integral elements in personality development. It is a framework that is flexible and applicable to any contemporary educational institutions. The third part of the paper discusses some implications of this renewed concept for contemporary educational system. The study utilizes the ‘grounded theory’ which is a qualitative approach that generates theory from observation. It is hoped that this conceptual study would lead to the reformulation of educational aims, a more careful selection of curricular contents, as well as the application of pedagogical methods and mode of evaluation for contemporary educational institutions.